KONSEP PENDIDIKAN ANAK USIA SEKOLAH DASAR (6-12) TAHUN DI LINGKUNGAN KELUARGA MENURUT PENDIDIKAN ISLAM - Yahya, Usman (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2015)
How is The concept of education of children primary school age (6-12) years in a family environment according to Islamic education? This formulation is detailed within the following limits: (1) What educational preparation of primary school age children (6-12) years in a family environment according to Islamic education, and (2) what materials and methods used in the education of parents of primary school age (6-12 ) years in a family environment education according to Islam The usefulness of this study were (1) provide insight to scientists information and about the education of children in the womb, (2) provide intellectual insight, especially to the mother and the father to educate elementary school-age children (6- 12) years in a family environment. Results in discussion are: (1). Preparatory education of children of primary school age (6-12) years in a family environment according to Islamic education is very important. Children at this age have already started critical and can do so directly with the good. Therefore, parents must understand the family environment and prepare for what materials and how to carry out the education of children of this age. (2) Materials and methods of primary school age children (6-12) years in a family environment according to Islamic education is also very important. Parents should know the educational material that will be given to their children well and parents also do it correctly.Â Konsep pendidikan anak usia sekolah dasar (6-12) tahun di lingkungan keluarga menurut pendidikan Islam? Rumusan ini dirinci dalam batasan berikut: (1) Apa persiapan pendidikan anak usia sekolah dasar (6-12) tahun di lingkungan keluarga menurut pendidikan Islam, dan (2) apa materi dan metode yang digunakan orangtua dalam pendidikan usia sekolah dasar (6-12) tahun di lingkungan keluarga menurut pendidikan Islam. Kegunaan penelitian ini adalah (1) memberikan informasidan wawasan terhadap para ilmuwan tentang pendidikan anak dalam kandungan, (2) memberikan wawasan intelektual terutama kepada ibu dan ayah untuk mendidik anak usia sekolah dasar (6- 12) tahun di lingkungan keluarga. Hasil bahasan yang ditemuakan adalah: (1). Persiapan pendidikan anak usia sekolah dasar (6-12) tahun di lingkungan keluarga menurut pendidikan Islam adalah sangat penting. Anak pada Usia ini sudah mulai kritis dan dapat melakukannya secara langsung dengan baik. Untuk itu, orangtua dilingkungan keluarga harus mengerti dan mempersiapkan materi apa dan bagaimana melakukan pendidikan terhadap anak usia ini. (2) Materi dan metode anak usia sekolah dasar (6-12) tahun di lingkungan keluarga menurut pendidikan Islam juga sangat penting. Orangtua hendaknya mengetahui materi pendidikan yang akan diberikan kepada anaknya dengan baik dan orangtua juga melakukannya dengan dengan tepat.